166 A Comparison of key Methodologies Used to Quantify Protein Quality in Mammals: Ileal Digestibility, Indicator Amino Acid Oxidation, and in Vitro Digestibility. (21st September 2022) - Cargo-Froom, Cara; Columbus, Daniel A; Kiarie, Elijah; Marinangeli, Christopher; Shoveller, Anna-Kate
Abstract: There are several methodologies which can be used to measure protein quality of an ingredient, however, the results of these studies are generally not compared to one another. The objectives of these studies were to 1) determine standardized ileal digestibility (SID) and in vitro digestibility coefficients for protein and amino acids (AA) from select pulses; 2) determine metabolic availability (MA) of methionine (Met) from field peas and faba beans; and, 3) compare digestibility coefficients determined via different methods. To determine SID of pulses, ileal cannulated barrows were randomly assigned to diets in a 4×4 Latin square. A nitrogen free diet was used to measure basal endogenous losses of AA and protein. Metabolic availability was determined via indicator AA oxidation by applying the principle of slope-ratio assay to F 13 CO2 from phenylalanine oxidation quantified through CO2 collection during breath collection using indirect calorimetry with barrows randomly assigned to diets in a 10×10 Latin square. Dietary treatments were formulated to include graded levels of Met: crystalline AA diets (Met inclusion of 50, 60, 70, and 80% of requirement), and pulse test diets (Met inclusion of 60, 70, and 80% of requirement). In vitro digestibility of diets was conducted using the TNO-gastrointestinal model. Statistical analysis of SID data was conducted using a mixed model in SAS with diet as a fixed effect and pig and period as random effects. Means were separated using Tukey HSD. Statistical comparison for digestibility coefficients compared to one another and compared to MA coefficients of Met will be conducted once all IAAO and in vitro data are finalized. The SID coefficients for protein and indispensable amino acids are summarized in Table 1. Peas had lower threonine content compared to faba beans and lentils (P < 0.05). Determination of in vitrodigestibility and MA of Met is in progress.